Study on synthesis of some new derivatives of Malloapelta B isolated from Mallotus apelta - Nam, Nguyen Hoai; Tung, Nguyen Huu; Nhiem, Nguyen Xuan; Minh, Chau Van; Kiem, Phan Van (Vietnam Journal of Chemistry, 2014)
Six new benzopyran derivatives were synthesized by reduction reaction and Michael reaction from malloapelta B. Their structures were determined as 8-(1’-oxo-butyl)-5,7-dimethoxy-2,2-dimethyl-2H-1-benzopyran (2), 8-(1’-oxo-3’(R)-methyl-4’-acetyl-5’-oxo-hexyl)-5,7-dimethoxy-2,2-dimethyl-2H-1-benzopyran (3), 8-(1’-oxo-3’(R)-methyl-4’(S/R)-(methyl fomiate)-5’-oxo-hexyl)-5,7-dimethoxy-2,2-dimethyl-2H-1-benzopyran (4,4’), 8-(1’-oxo-3’(R)-methyl-4’(S/R)-(ethyl formiate)-5’-oxo-hexyl)-5,7-dimethoxy-2,2-dimethyl-2H-1-benzopyran (5,5’) by spectroscopic data, including two-dimensional NMR techniques and ESI spectrum.Keywords: Malloapelta B; Michael reaction; reduction reaction; 5,7-dimethoxy-2,2-dimethyl-2H-1-benzopyran.